(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2019)
Non-volatile acids including lactic acid and pyruvic acid, hydrochloric acid, sulphuric acid and phosphoric acid are produced during metabolic process.About50-150Eq of inorganic acid are flashed out through kidney in 24 hours. These acids are partially buffered with cations ,large amount of sodium in the distal tubules of the kidney some of the cations get reabsorbed and PH of the URINE falls .Kidney can buffer acids and conserve fixed bases in the production of ammonia from amino acid. It plays role to neutralize acids when they are formed in excess .In kidney disease ,tubular reabsorption of sodium in exchange for hydrogen and there occurs excessive retention of phosphates and sulphates .As acidosis takes place. It means it causes renal diseases, poisoning by an acid salt, and excessive loss of intestinal fluid and excessive losses of electrolyte.